INDIKATOR STRUKTURAL DAN KULTURAL DALAM MEMAHAMI KEMISKINAN MASYARAKAT NENOTES KECAMATAN SANTIAN KABUPATEN TIMOR TENGAH SELATAN - Tun, Meriam; Servatius, Rodriques; Boro, Veronika I.A. (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This study focuses on examining structural and cultural indicators in understanding poverty among the people of Nenotes Village, Santian District, South Central Timor Regency. Using a descriptive qualitative method, the main research question is how structural and cultural indicators are manifested in understanding poverty in Nenotes Village. To analyze this issue, various measures from welfare theory are applied to capture the social and economic conditions of the community. The results show that structural indicators are related to policies that do not favor the people, income inequality, limited employment opportunities, and uneven economic structures. Meanwhile, cultural indicators are associated with individual behaviors such as laziness, low levels of education, and school dropout rates, as well as social behaviors including a consumptive culture, family burdens, and a lack of public awareness to improve welfare (an easy-going culture). Efforts to overcome poverty in Nenotes Village can be carried out by improving the quality of education and providing skills training for the community. The government needs to create broader employment opportunities and support the development of productive local enterprises. In addition, encouragement is needed for the community to change their mindset to become more independent and oriented toward improving welfare